Improving Staff Knowledge and Confidence in Lithium Counselling to Enhance Patient Safety and Standardise Practice Across Community Mental Health Teams - Ella Bauwens; Nazim Zaim; Yousof Osman; Khyati Patel; Nirvana Islam (BJPsych Open)
Aims: The 2019–20 Community Pharmacy Quality Scheme audit concluded 34% of audited patients were unfamiliar with lithium toxicity symptoms, where 29% were unaware of how to prevent it, highlighting the gap in effective patient education. Our preliminary research revealed that 50% of medical professionals lacked confidence in providing lithium counselling with 41% being either unaware or unsure of how to counsel a patient if they had missed a dose. Therefore, we aim to tackle staff knowledge and improve abilities in lithium counselling to enhance patient safety and understanding, ultimately leading to fewer incidences of toxicity and harm.